Investigating Preventive Behaviors Toward COVID-19 Among Iranian People - Baghernezhad Hesary, Fatemeh; Salehiniya, Hamid; Miri, Mohammadreza; Moodi, Mitra (Frontiers in Public Health, 2021)
Background: Considering the importance of preventive behaviors in reducing the transmission of COVID-19, this study was conducted to determine the preventive behaviors toward the spread of COVID-19. Methods: This cross-sectional study was performed 7 weeks after the confirmation of the first case of Covid-19 by the Ministry of Health and Medical Education in Iran. Data were completed online using a researcher-made questionnaire, the validity and reliability of which were confirmed, for 1,200 Iranians from 8 April 2020 to 9 May 2020. Results: The mean age of study participants was 37.77 ± 11.20 years. The mean score of preventive behaviors was 62.67 ± 8.53. The results showed that there was a significant relationship between the variables of gender, education, economic status, and preventive behaviors of COVID-19. The highest frequency is related to not using hookah and cigarettes and then avoiding losing and rubbing (78%) and the lowest percentage is related to exercising behavior (16%). Conclusion: Due to the low level of prevention behaviors during the outbreak of the disease, it is important to design educational and supportive interventions to improve and perform coronavirus prevention behaviors with more focus on men, illiterate people, and poor economic status.